The Effects of Micro-influencers on Customer Purchase Intention towards Fashion Products on Instagram - Jabrayilov, Fehruz (ADA University, 2022)
The main purpose of this research paper is to analyze the effect of social media micro influencer shared content on consumers’ purchase intention towards fashion products on Instagram. To analyze this effect, relationship among trustworthiness, expertise, likability, similarity and familiarity of the micro influencers with purchase intention of consumers have been selected has variables in this paper based on source credibility and source attractiveness models. The formulated hypotheses have been tested using obtained cross sectional survey from 218 respondents who follow social media micro Influencers on Instagram. Regression analyses have been made using STATA to find whether there exists positive relationship among variables. As a result of this study, it has been found that expertise, likability, similarity and familiarity of social media micro influencers have a positive impact on consumers’ purchase intentions. However, no statistically significant relationship between trustworthiness of micro influencers and consumer purchase intentions has been found in this study.
Keywords: Influencer marketing.; Social media.; Instagram.; Purchase intention.; Business